2002
DOI: 10.1103/physrevlett.88.161802
|View full text |Cite
|
Sign up to set email alerts
|

ϒProduction and Polarization inpp¯Collisions at

Abstract: We report on measurements of the 1S, 2S and 3S di erential cross sections d 2 =dp T dy jyj 0:4 , as well as on the 1S polarization in pp collisions at p s = 1:8TeV using a sample of 77 3 pb ,1 collected by the Collider Detector at Fermilab.The three resonances were reconstructed through the decay ! + , . The measured angular distribution of the muons in the 1S rest frame is consistent with unpolarized meson production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 135 publications
(37 citation statements)
references
References 24 publications
2
32
0
3
Order By: Relevance
“…They are also in agreement [19][20][21] with the existing data from RHIC [22] energy all the way up to that of the LHC [23][24][25][26][27][28][29][30]. CO channels are most likely not needed to account for low P T data -and thus for the P T integrated yields.…”
Section: Introductionsupporting
confidence: 75%
“…They are also in agreement [19][20][21] with the existing data from RHIC [22] energy all the way up to that of the LHC [23][24][25][26][27][28][29][30]. CO channels are most likely not needed to account for low P T data -and thus for the P T integrated yields.…”
Section: Introductionsupporting
confidence: 75%
“…According to the NRQCD factorization approach [4], these matrix elements are universal constants which are independent of the short-time production processes, and need to be determined from data. Calculations based on the colour-singlet model [6][7][8] show good agreement [9][10][11][12][13][14] with the experimental data [15][16][17][18][19][20][21][22] for production cross-sections and the shapes of the transverse momentum spectra. However, this approach fails to describe the spin-alignment (usually labelled as polarization) of S-wave charmonium states [23,24].…”
Section: Introductionmentioning
confidence: 88%
“…The measured fractions of Υ mesons originating from χ b decays are large, around 30 − 40 % [28], for Υ mesons with high transverse momenta, p Υ T 20 GeV/c. Experimentally, polarization of Υ mesons produced in high-energy hadron-hadron interactions was studied by the CDF collaboration in pp collisions at √ s = 1.8 and 1.96 TeV [16,31]. It was found that the angular distributions of muons from Υ → µ + µ − decays for all three Υ states are nearly isotropic in the central rapidity region y Υ < 0.6 and p Υ T < 40 GeV/c [31].…”
Section: Jhep12(2017)110mentioning
confidence: 99%
“…Такая кинематика t-канальных парто-нов соответствует МРК частиц, рождённых в жёстком процессе. В наших предыдущих работах [33][34][35][36][37][38], посвящённых процессам рождения тяжёлых кваркониев, мы показали, что эти неинтегрированные ФР КМР дают луч-шее описание p T −спектров, измеренных на Тэватроне [50][51][52][53][54][55][56] и БАК [57][58][59].…”
Section: в работе рассматривается инклюзивное рождение очарованныхunclassified